Pd-N-heterocyclic carbene complex catalysed C–H bond activation of 2-isobutylthiazole at the C5 position with aryl bromides. (22nd March 2021) - Khan, Siraj; Buğday, Nesrin; Yaşar, Sedat; Ullah, Naseem; Özdemir, İsmail
Abstract : An effective and efficient catalytic system has been reported for the synthesis of C5-arylated 2-isobutylthiazoles. Abstract : An effective and efficient catalytic system has been reported for the synthesis of C5-arylated 2-isobutylthiazoles. Pd-N-heterocyclic carbene complexes like [Pd(μ-Cl)Cl(SIPr)]2 (2 ) and (L Cl2 Pd-SIPr) (3 : L = PPh3, 4 : L = Py; 5 : L = 3-CHO-Py) were synthesized and characterized by 1 H, 13 C, 31 P NMR, LC-MS/MS, elemental analysis, and FTIR spectroscopy. These Pd-N-heterocyclic carbene complexes were assessed for the first time as catalysts for the C–H arylation reaction of 2-isobutylthiazole at the C5 position with different (hetero)aryl bromides. The catalytic system showed a low catalyst loading (1 mol%) and did not require the use of additional additives such as pivalic acid. The catalytic system developed with these catalysts enables the synthesis of fine chemicals in high yields under aerobic or anaerobic conditions. All complexes showed moderate to good yields in the C5 direct arylation of 2-isobutylthiazole, while complex 2 exhibited higher catalytic activity than the other complexes.